Bibliotecas vivas resistem: ações promovidas pela Biblioteca Sinhá Junqueira no combate às desigualdades - Santos, Gabriele da Silva (Universidade Federal de São Carlos, 2024)
The aim of this paper is to understand the impact of the "living library" model, which is geared towards combating the inequalities of minorities and vulnerable groups. We will defend the living library model as a library format that provokes resistance from people who have historically been excluded from their rightful democratic spaces. The model aims to respond to these demands through access to information, education, literature and participation in decision-making. Therefore, based on the partial case study of the Sinhá Junqueira Library, we will present the socio-cultural actions that serve and represent this section of society, and which are based on the Sustainable Development Goals and the IFLA- UNESCO 2022 Public Library Manifesto. The research is based on an exploratory and qualitative bibliographic review, with an extensive search for literature on "living libraries" and information mediation. It was possible to observe the importance of the practice of information mediation carried out in favor of social protagonism, aiming to increase the participation of different minority groups in the construction of the BSJ, which implies the improvement of the lives of the subjects of these groups. We conclude that the living library is a non-traditional, contemporary library model that expands the horizons for the debate on the future of libraries and contributes to reducing inequalities.
Living libraries resist: actions promoted by the Sinhá Junqueira Library to combat inequalities
Keywords: Bibliotecas vivas; Grupos vulneráveis; Biblioteconomia Social; Living libraries; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO